Cascade C–C and C–N Bond Formation: A Straightforward Synthesis of Phenanthridines and Fused Quinolines. Issue 12 (6th April 2016) - Borah, Ashwini; Gogoi, Pranjal
Abstract: A Pd‐catalyzed cascade process has been developed for the synthesis of quinoline and phenanthridine derivatives from various β‐chloro α, β‐unsaturated aldehydes and 2‐chloroaryl aldehydes, respectively, in good to high yields. The reaction proceeds through Pd‐catalyzed cascade carbon–carbon and carbon–nitrogen bond formation in a single reaction vessel. The requisite β‐chloro α, β‐unsaturated aldehydes were efficiently synthesized from their corresponding carbonyl compounds. The use of the ligand Sphos with Pd(OAc)2 is crucial for the successful implementation of the present cascade process. This synthetic protocol is also applied for the gram‐scale synthesis of a trispheridine alkaloid. Abstract : A Pd‐catalyzed cascade process has been developed for the synthesis of quinoline and phenanthridine derivatives. The reaction proceeds through carbon–carbon and carbon–nitrogen bond formation in a single reaction vessel. The use of the ligand Sphos with Pd(OAc)2 is crucial for the implementation of the cascade process. The gram‐scale synthesis of trispheridine alkaloid is also described.